Socialization of The Use of Melinjo Leaf Ethanol Extract (Gnetum gnemon L.) on Growth Salmonella typhi Bacteria - Syarifuddin, Aminah; Pranata, Chandra; Boru Situmorang, Novidawati; Octora, Debi Dinha; Ramadhani, Lili (JURNAL PENGMAS KESTRA (JPK), 2023)
Gnetum gnemon L. has antibacterial activity against Salmonella typhi because it contains flavonoids, saponins, tannins, alkaloids, and steroids. Where these compounds play an important role as an antibacterial. The purpose of this service is to provide information to the public regarding the benefits of melinjo leaves which can act as an antibacterial agent. This service activity is carried out in the form of socialization using lecture, question and answer, and demonstration methods. The number of participants in this community service activity was 20 pharmacists at Grandmed Lubuk Pakam Hospital. Based on the results of the PkM activities carried out, it can be stated that there has been an increase in public knowledge regarding the efficacy of melinjo leaves as an antibacterial substance. This can be proven by the increase in post-test scores when compared to pre-test scores. The average increase in the knowledge of PkM participants was 21.5. On the other hand, the highest post-test score obtained was 85, while the lowest post-test score was 60. Meanwhile, based on the PkM material that had been socialized, the PkM participants understood that the results of phytochemical tests on melinjo leaf Simplicia showed that melinjo leaf extract contains compounds alkaloids, flavonoids, steroids, saponins, and tannins. Meanwhile, the antibacterial test showed that the inhibition zones of various concentrations included a moderate concentration of 40%, a moderate category of 60%, and a strong category of 80%. The average diameter of the inhibition zone increased with each concentration of melinjo leaves.